Plate Q: Pyrotechnic set piece of a dragon - Siemienowicz, Kazimierz (Artis Magnae Artilleriae, 1650)
Fig. 197: Wooden frame of dragon set piece. Fig. 198: Disposition of pyrotechnics in the dragon frame. Fig. 199: Outward appearance of dragon set piece.
Keywords: Artillery; Fireworks